Maternal race/ethnicity as a risk factor for cervical insufficiency. (February 2018) - Tanner, Lisette D.; Tucker, Lue-Yen; Postlethwaite, Debbie; Greenberg, Mara
Abstract: Background: Preterm birth (PTB) affects 1 in 9 pregnancies in the United States. There are well known but poorly understood racial/ethnic disparities in PTB rates. The role that racial/ethnic disparities in cervical insufficiency (CI) may play in the overall disparities in preterm birth rates is unknown. Objective: The primary objective of this study was to examine racial/ethnic differences in risk of CI. Study design: We conducted a retrospective cohort study of singleton pregnant women in 2012 who were members of Kaiser Permanente Northern California (KPNC), excluding elective termination, delivery outside KPNC, and loss to follow-up. The primary outcome was CI; the secondary outcomes included stillbirth, PTB, and neonatal intensive care unit (NICU) admission. We compared rates of these outcomes among women of different racial/ethnic background. Multivariable logistic regression modeling was used to assess other potential risk factors for CI, including maternal age, parity, medical co-morbidities, prior cervical procedures, prior pregnancy terminations, and history of PTB. Results: A total of 34, 173 women who were pregnant in 2012 were included in the study. The racial/ethnic makeup of the cohort was 38.6% White, 25.8% Asian, 25.1% Hispanic, 7% Black, and 3.5% other. Approximately 1% (401) of women were diagnosed with CI. Black women had a significantly higher rate of CI (3.2%) compared to White women (0.9%, P <  0.001) as well as higher rates of PTB (9.2%). Infants born to black women had higher rates of NICU care (8.7%) compared to other racial/ethnic groups. Regression analysis showed that Black race/ethnicity was significantly associated with CI compared to Whites (OR 2.89, 95% CI 2.13–3.92) after controlling for other variables associated with CI. Conclusion: Black women had higher odds of CI compared to White women. This disparity may contribute to the significantly higher rate of PTB among Black women nationally. Further investigation of this association may provide important contributions to our understanding of both CI and PTB.